Relationship between sex hormone levels, bone mineral density and bone turnover markers in healthy moroccan men: a cross-sectional study - El Maataoui, Aissam (Pan Afr Med J, 2015)
INTRODUCTION: Gonadal steroid hormones play a crucial role during skeletal growth and maturation in both men and women. The aim of this study is to evaluate the relationship of sex hormone levels, bone mineral density and biochemical markers of bone turnover in healthy Moroccan men. METHODS: 142 Moroccan men who had no previous diagnosis of osteoporosis were enrolled prospectively in this cross-sectional study between December 2009 and August 2010. Also, subjects were excluded from the study if they had conditions affecting bone metabolism. Different biochemical parameters were assayed: Testosterone, Estradiol, sex hormone binding globulin, Osteocalcin, vitamin D, crosslaps, intact parathyroid hormone and alkaline phosphatase. Dual-energy X-ray absorptiometry was used to measure the Bone mineral density (BMD) (g/cm(2)). RESULTS: In this study, among the 142 Moroccan men, 29 (20.1%) had densitometry osteoporosis and the prevalence of vitamin D insufficiency was 94%. No correlation was found between Estradiol, Testosterone and bone mineral density but we found significant differences in the levels of Estradiol between patients with osteoporosis, osteopenia and normal patients. Bone mineral density at the lumbar spine was negatively correlated to hormone-binding globulin and positively correlated to free androgen index, free estrogen index and the Body mass index. BMD at the total hip was positively correlated to free androgen index, Body mass index and negatively correlated to sex hormone binding globulin, alkaline phosphatase, intact parathyroid hormone, osteocalcin, Crosslaps and age. CONCLUSION: Our study showed that increasing age, intact parathyroid hormone and alkaline phosphatase levels and decreasing body mass index were the most important independent factors associated to the presence of a low BMD at the total hip. Increasing body mass index and free androgen index level were the most important independent factors associated to the presence of a low BMD at the lumbar spine. The combination of variable that best predicted the male osteoporosis is age, body mass index, alkaline phosphatase and cigarette smoking.